Hydrometrocolpos Presenting as Abdominal Distension in the Newborn - Arora, Sunita; narang, gursharan singh; Khurana, Mandeep Singh; Khera, Anubha (Journal of Nepal Paediatric Society, 2013)
Hydrometrocolpos is a rare entity in the newborn period with an incidence of 1 in 16000 female deliveries. We report a rare case of a two days old female child who presented to us with marked abdominal distension at birth due to hydrometrocolpos. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7515 J Nepal Paediatr Soc. 2013; 33(2):136-137